The Future of Clinical Pharmacy: Developing a Holistic Model - Patricia A. Shane; Eleanor Vogt (MDPI AG, 2013)
This concept paper discusses the untapped promise of often overlooked humanistic skills to advance the practice of pharmacy. It highlights the seminal work that is, increasingly, integrated into medical and nursing education. The work of these educators and the growing empirical evidence that validates the importance of humanistic skills is raising questions for the future of pharmacy education and practice. To potentiate humanistic professional competencies, e.g., compassion, empathy, and emotional intelligence, how do we develop a more holistic model that integrates reflective and affective skills? There are many historical and current transitions in the profession and practice of pharmacy. If our education model is refocused with an emphasis on pharmacy's therapeutic roots, the field has the opportunity to play a vital role in improving health outcomes and patient-centered care. Beyond the metrics of treatment effects, achieving greater patient-centeredness will require transformations that improve care processes and invest in patients' experiences of the treatment and care they receive. Is layering on additional science sufficient to yield better health outcomes if we neglect the power of empathic interactions in the healing process?